Alterations of ROS pathways in scleroderma begin at stem cell level - Orciani, M; Svegliati, S; Gorbi, S; Spadoni, T; Lazzarini, R; Regoli, F; Di Primio, R; Gabrielli, A (Journal of biological regulators and homeostatic agents, 2013)
Scleroderma is a chronic systemic autoimmune disease (primarily of the skin) characterized by fibrosis (or hardening), vascular alterations and autoantibodies production.There are currently no effective therapies against this devastating and often lethal disorder. Despite the interest for the immunomodulatory effects of mesenchymal stem cells (MSCs) in autoimmune diseases, the role of MSCs in scleroderma is still unknown. A pivotal role in scleroderma onset is played by oxidative stress associated with the accumulation of great amounts of reactive oxygen species (ROS). This study depicts some phenotypic and functional features of MSCs isolated from the skin of healthy and scleroderma patients; the ROS production and accumulation, the expression of ERK1/2 and the effects of the stimulation with PDGF, were analyzed in MSCs; results were compared to those observed in primary fibroblasts (Fbs) isolated from the same subjects. We found that the pro-oxidant environment exerted by scleroderma affects MSCs, which are still able to counteract the ROS accumulation by improving the antioxidant defenses. On the contrary, scleroderma fibroblasts show a disruption of these mechanisms, with consequent ROS increase and the activation of the cascade triggered by scleroderma auto-antibodies against PDGFR.